Annual Plan 1988-89 Government of Karnataka - Planning Commission (Planning Commission, 1988)
The State has drawn up an ambitious programme for the Seventh Five Year Plan. But, almost continuous droughts during the first three years of the Plan and chronic power shortages have adversely affected the development efforts towards achieving the objectives of the Seventh Plan. The very first year of the Plan witnessed one of the severest droughts in recent years. During the second year, 1986-87, there was only a partial recovery in the economy. The State’s economy has again suffered a severe setback during 1987-88 due to failure of rainfall and continued power shortages.
Planning Department